Numerical modeling of radiation-induced charge neutralization in MOS devices - Sambuco Salomone, Lucas Ignacio; García Inza, Mariano Andrés; Carbonetto, Sebastián Horacio; Lipovetzky, José; Redin, Eduardo Gabriel; Faigon, Adrián Néstor (Pergamon-Elsevier Science Ltd, 2022)
Fil: Sambuco Salomone, Lucas Ignacio. Universidad de Buenos Aires. Facultad de Ingeniería. Departamento de Física. Laboratorio de Física de Dispositivos Microelectrónica; Argentina